Morpho-Molecular Characterization and Screening of Rice (Oryza Sativa L.) Genotypes for Salinity Tolerance at Seedling Stage (SAARC Journal of Agriculture, 2021)
Salinity is one of the major abiotic stresses which severely affect the production of crops across the world. Twenty rice genotypes of diverse origins were assessed to examine salt tolerance potentiality at seedling stage as well as to elucidate the genetic variation using SSR markers. Consequently, IRRI standard protocol was applied to screen out those varieties for tolerance at the glasshouse laboratory of Bangladesh Institute of Nuclear Agriculture, maintaining salt stress level at 6dS m-1, 8dS m-1, 10dS m-1 and 12 dS m-1. Data on morphological parameter were recorded as shoot length (cm), root length (cm) and total dry matter (TDM). For molecular characterization thirteen SSR markers were exploited to determine the genetic diversity and in this context, 53alleles were revealed while the mean number of alleles per locus was 4.The Polymorphism Information Content (PIC) value ranged from 0.37- 0.78 having an average of 0.58. The Un-weighted Pair Group Method with Arithmetic Mean (UPGMA) displayed three major clusters including some sub-clusters, where in Cluster 1, Binadhan- 8, Binadhan-10, Pokkali and FL478 were very close in their vicinity. Information obtained from this experiment, thus can be taken into account for stress breeding program and prospective genetic materials could be utilized for exploring the genetic architecture in favor of salt tolerance as well as for developing better salt tolerant rice varieties in near future.SAARC J. Agri., 18(2): 1-15 (2020)